A curated dataset on the distribution of West Palaearctic freshwater bivalves - Manuel Lopes-Lima; David C. Aldridge; María G. Álvarez; Rafael Araujo; José Miguel Barea-Azcón; Ani Bikashvili; Dolores Bragado; Lilia Bylyna; Anna Carlevaro; Ján Černecký; Frédéric Cherot; Anna Cichy; et al. (Scientific Data)
Abstract Freshwater bivalves (FWB) are attracting scientific and societal attention given their essential ecosystem services, ecological functions, and poor conservation status. Current knowledge of the spatial distribution of West Palearctic FWB is poor preventing the understanding of biogeography and conservation planning. One of the priorities of the pan-European networking project “CONFREMU - Conservation of freshwater mussels: a pan-European approach” funded by the European Union, was to fill the knowledge gap on the distribution of FWB in Europe and adjacent regions. Based on the efforts of this network of scientists, we provide the most complete, taxonomically, and geographically accurate distribution of FWB species for the entire West Palearctic. The dataset contains 270,287 geo-referenced records of 93 native and 8 non-native FWB from 1674 to 2023. The dataset compiles information from private records from 82 specialists and multiple sources (e.g., published articles, grey literature, biodiversity databases, and scientific collections). This dataset, available online, represents an important data source for future studies on the biodiversity, biogeography, and conservation of these important organisms.